Users Acceptance of E-Government System in Sintok, Malaysia: Applying the UTAUT Model - Anisa Safiah Maznorbalia; Muhammad Aiman Awalluddin (Policy & Governance Review, 2021)
E-government services have become a vital tool to provide citizens with more accessible, accurate and high-quality services and information. E-government system provides an efficient dissemination of information to people and eases people to communicate directly with government services. The utilization of ICT through e-government enhancing efficiency and effectiveness of service delivery in the public sector. The system is regarded as one of the vital elements to be a developed country. The application of e-government indicates the readiness and ability of the nation utilizing technology within public administration periscope. Although the Malaysian government has introduced e-government for many years, its acceptance still not very high. Therefore, this paper studies the key factors of Malaysian citizens’ in Sintok, Kedah, a semi- rural area on approval on e-government services based on the Unified Theory of Acceptance and the Use of Technology (UTAUT Model). The survey data was collected from 83% respondents to measure people understanding and awareness toward e-government system. The results show that there is an excellent understanding among Malaysian towards e-government system.